The professional growth needs of vocational teachers in secondary fishery schools - Alcera, Vicente B. 1927-
Professional growth needs of vocational teachers in secondary fishery schools were determined in this study. Comprehensive information and data concerning the educational qualifications and service status of fishery teachers; their needs for improvement in the areas of teaching skills, technical knowledge and skills and other professional abilities; and the activities and problems they encountered in striving for professional growth were presented in this study.